Perbandingan Hasil Belajar PAI Model Pembelajaran Rotating Trio Exchange dengan Numbered Head Together - Wulantika Yuliani; Wedra Aprison; Darul Ilmi; Arifmiboy Arifmiboy (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this author's research is to see the comparison of students' PAI learning outcomes using the Rotating Trio Exchange (RTE) and Numbered Head Together (NHT) learning models at SMP Negeri 1 Banuhampu in class VII students and compare PAI learning outcomes with the two learning models. The type of research used is experimental with a quantitative approach. The population was all seventh grade students consisting of 9 classes and a total of 275 students. The sample in this study used random techniques, obtained 2 classes that became samples with details of 58 students. The classes taken were VII.1 and VII.2. Data were collected through the scores of students' PAI learning outcomes obtained through the PAI learning outcomes test in the form of multiple choice. The results of the research that has been done, the results show that there are learning outcomes of students who use the RTE learning model have been above the KKM value of 76. And the learning outcomes of students who use the NHT learning model have been above the KKM score of 76. And there is also a significant difference in the PAI learning outcomes of students in the RTE learning model with the method of Shapiro Wilk at sig 0.05, as well as the NHT learning model.